The Existence of Memorising al-Qurân in Islamic University: Motivation, Methods, and Achievements - Agus Maimun; Muhamad Yasin (Didaktika Religia, 2019)
In the Islamic University lately, there is a growing awareness to memorise the Qurâ€™an. This phenomenon continues to develop along with the various open opportunities provided by the manager of higher education for those who memorise the Qurâ€™an. This research will focus on the motivation to memorise the Qurâ€™an, the method of memorising the Qurâ€™an, and the achievements of students memorising the Qurâ€™an. This research is descriptive. The use of interview, observation, and documentation methods and analysis of reflective data in research has enabled him to understand more deeply about the existence of memorising the Qurâ€™an. The results showed that studentsâ€™ motivation in memorising the Qurâ€™an was inspired by people who memorised the Qurâ€™an first, especially families who had indeed been directed so that all family members memorised the Qurâ€™an and also wanted to get virtue from rote learning al-Qurâ€™an. The method of memorising the Qurâ€™an used is al-nazar or tarÄ«qat takrÄ«r al-qirÄat al-juzâ€™Ä« (read repeatedly or slowly) while still maintaining the tradition of using the genealogy of the cleric or clerics to one another continuously. Al-Qurâ€™an memorisation students achieved an average of 3.46 from the 0-4 interval, but most of them were above 3.5.